Strengthening Village-Owned Enterprises for Sustainable Tourism Development: Memperkuat Usaha Milik Desa untuk Pengembangan Pariwisata Berkelanjutan - Khairunnisa, Khansa; Sukmana, Hendra (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Village-Owned Enterprises (BUMDes) serve as a strategic instrument for rural economic empowerment in Indonesia. Specific Background: In Ketapanrame Village, Sidoarjo Regency, the Sumber Gempong tourism object managed by BUMDes has shown growing economic potential through community-based tourism management. Knowledge Gap: Despite increasing local participation, the sustainability of BUMDes operations and their managerial governance remains underexplored. Aims: This study aims to analyze the role of BUMDes in developing local tourism and improving community welfare. Results: The findings reveal that BUMDes effectively mobilized local resources, improved tourism services, and strengthened social capital, although challenges remain in human resource management, marketing strategy, and legal reinforcement. Novelty: This research highlights the integration between institutional governance and community collaboration as a key driver of sustainable rural tourism. Implications: Strengthening administrative capacity, digital marketing, and legal formalization of BUMDes are crucial to ensure its long-term contribution to rural economic development. Highlights: Community-based management increases local welfare. BUMDes contributes to sustainable tourism growth. Institutional governance determines tourism success.